2020
DOI: 10.1519/jsc.0000000000003736
|View full text |Cite
|
Sign up to set email alerts
|

Performance Differences Between the Arched and Flat Bench Press in Beginner and Experienced Paralympic Powerlifters

Abstract: Neto, FR, Dorneles, JR, Luna, RM, Spina, MA, Gonc ¸alves, CW, and Gomes Costa, RR. Performance differences between the arched and flat bench press in beginner and experienced Paralympic powerlifters. J Strength Cond Res 36 (7): 1936-1943, 2022-The present study aimed to verify the differences of the total load, trajectory of the barbell in the sagittal plane, and mean velocity of the barbell between the arched and flat techniques of the bench press in beginner (BG) and experienced (EG) Paralympic powerlifters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…In a study that evaluated the hypotensive effects in Paralympic athletes, no differences were observed between the two training sessions with different intensities, without significant interaction (training vs. time), and there was an increase in SBP immediately after training at both intensities, followed by a decrease to levels below resting values from 20 to 50 min after resistance training [ 2 ]. Other studies have presented similar results between conventional and Paralympic athletes in the bench press exercise of powerlifting [ 28 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 59%
“…In a study that evaluated the hypotensive effects in Paralympic athletes, no differences were observed between the two training sessions with different intensities, without significant interaction (training vs. time), and there was an increase in SBP immediately after training at both intensities, followed by a decrease to levels below resting values from 20 to 50 min after resistance training [ 2 ]. Other studies have presented similar results between conventional and Paralympic athletes in the bench press exercise of powerlifting [ 28 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 59%
“…This could help to explain the different activation herein between SCI and OD athletes. Moreover, when assessing whether there would be differences between the normal position vs. with the chest arched, it was found that there were no significant differences in total load, bar trajectory and average bar speed; indicating that greater support, as allowed in competitions with the use of a belt, may enable a greater stability for athletes [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are not many studies on PP athletes, and this is the first to validate a monitoring tool for strength training performance. Previous studies with this specific population have analyzed the effect of caffeine, placebo [34], Ibuprofen [35], and creatine [36] on performance and muscle damage; relationships between loading intensities [37] and trap stabilization on the bench [38] with movement velocities; the influence of the arched and flat technique [25], and grip width on strength outcomes [39]; the difference of warm-up on performance [40], and the post-exercise cardiovascular effects of two typical high-intensity resistance-training sessions [41]. The RIR scale is a practicable alternative for regular load monitoring.…”
Section: Discussionmentioning
confidence: 99%